Guided inquiry lab: Its effect to improve student’s critical thinking on mechanics - Febri, Ade; Sajidan, Sajidan; Sarwanto, Sarwanto; Harjunowibowo, Dewanto (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
Learning trends in the 21st-century require students to have the ability to sort appropriate information from certain sources. To do this, students must have critical thinking skills. One of the learning models that can facilitate students to think critically is a guided-inquiry lab. Thus, the purpose of this study was to quantitatively analyze the impact of the implementation of the guided-inquiry lab model on students' critical thinking skills on mechanics material. A pre-experimental method employing one group pretest-posttest only design was applied to obtain students' critical thinking skills data before and after the implementation of the guided-inquiry lab model. A total of 32 students from a junior high school in the city of Karanganyar, Central Java, were involved as the samples in this study. The data obtained were then analyzed using N-gain calculations. Based on the data analysis, there are 81.25% of students have medium creative thinking skills after being taught with a guided-inquiry lab, meaning there is an increase in the average score of students after being taught using a guided-inquiry lab model. It can be concluded that the implementation of the guided-inquiry lab model is effective to improve students' critical thinking skills